II-17 Lupus HDL promotes pro-inflammatory responses in macrophages through LOX1R binding and abrogation of ATF3 activity. (31st August 2016) - Smith, Carolyne K; Vivekanandan-Giri, Anuradha; Yuan, Wenmin; Playford, Martin P; Mehta, Nehal; Schwendeman, Anna; Pennathur, Subramaniam; Kaplan, Mariana J
Abstract : Background: Recent evidence indicates that high-density lipoprotein (HDL) exerts vasculoprotective activities by promoting activating transcription factor 3 (ATF3), leading to down-regulation of TLR-induced inflammatory responses. SLE is associated with increased cardiovascular disease (CVD) risk not explained by the Framingham risk score. Recent studies have indicated oxidised HDL as a possible contributor. We investigated the potential mechanisms by which lupus HDL may lose its anti-inflammatory effects and promote immune dysregulation. Methods and results: Compared to control HDL, SLE HDL activates NFK B, promotes inflammatory cytokine production, and fails to block TLR-induced inflammation in control macrophages. This failure of lupus HDL to block inflammatory responses is due to an impaired ability to promote ATF3 synthesis and nuclear translocation. SLE HDL-induced pro-inflammatory responses in macrophages are dependent on its binding to lectin-like oxidised low-density lipoprotein receptor 1 (LOX1R), which promotes suppression of ATF3 activity in a ROCK1/2 kinase-dependent manner. This inflammation can be modulated in vivo as lupus-prone mice exposed to the HDL mimetic ETC-642 show improved ATF3 induction and significant abrogation of pro-inflammatory cytokines Conclusions: Lupus HDL promotes pro-inflammatory responses, increased NFκB activity and decreased ATF3 synthesis and activity, in a LOX1R- and ROCK1/2 kinase-dependent manner. ETC-642 inhibited both in vitro and in vivo SLE HDL-induced inflammation. Acknowledgements: Funded by Intramural Research Program at NIAMS and by Lupus Research Institute.